2022
DOI: 10.3389/fonc.2022.859275
|View full text |Cite
|
Sign up to set email alerts
|

Lumiflavin Reduces Cisplatin Resistance in Cancer Stem-Like Cells of OVCAR-3 Cell Line by Inducing Differentiation

Abstract: Ovarian cancer stem-like cells (CSCs) play a vital role in drug resistance and recurrence of ovarian cancer. Inducing phenotypic differentiation is an important strategy to enhance the effects of chemotherapy and reduce the drug resistance of CSCs. This study found that lumiflavin, a riboflavin decomposition product, reduced the development of CSC resistance and enhanced the chemotherapy effect of cisplatin (DDP) on CSCs in DDP-resistant ovarian cancer OVCAR-3 cell line (CSCs/DDP) and was related to the induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…It was shown that a greater IC50 of CDDP was detected in PKM2-deficient HNSC cells compared with their normal counterparts (Figure 4A). As numbers of studies found that cell stemness/differentiation may contribute to chemoresistance in cancers [51,52], negative correlations between PKM2 expression and stemness markers, including Sox2, CD24, and Prom1/CD133 mRNA levels, were detected in subjects from the TCGA-HNSC dataset (Figure 4B). In contrast, the expression of the epithelial differentiation marker involucrin (IVL) was downregulated in PKM2-silencing HNSC cells compared with their counterpart (Figure 4C).…”
Section: Pkm2 Loss Modulated Chemosensitivity In Hnsc Cellsmentioning
confidence: 97%
“…It was shown that a greater IC50 of CDDP was detected in PKM2-deficient HNSC cells compared with their normal counterparts (Figure 4A). As numbers of studies found that cell stemness/differentiation may contribute to chemoresistance in cancers [51,52], negative correlations between PKM2 expression and stemness markers, including Sox2, CD24, and Prom1/CD133 mRNA levels, were detected in subjects from the TCGA-HNSC dataset (Figure 4B). In contrast, the expression of the epithelial differentiation marker involucrin (IVL) was downregulated in PKM2-silencing HNSC cells compared with their counterpart (Figure 4C).…”
Section: Pkm2 Loss Modulated Chemosensitivity In Hnsc Cellsmentioning
confidence: 97%